0581 Designing A Community-engaged Intervention To Address Sleep Apnea Health Disparities: The Tailored Approach To Sleep Health Education (TASHE). (27th April 2018) - Rogers, A; Robbins, R; Senathirajah, Y; Rapoport, D M; Allegrante, J; Ogedegbe, G; Williams, N; Bademosi-Kalinowski, J; Chung, A; Aird, C; Jean-Louis, G
Abstract: Introduction: Sleep apnea is characterized by repeated breathing pauses during sleep. Black/African Americans are at greater risk for sleep apnea than other racial/ethnic groups. The current study utilized a comprehensive approach with multiple key stakeholders to tailor health messages to black/African American individuals about sleep apnea. Methods: We used a comprehensive approach that engaged stakeholders (patient, community, and provider). Data collection included focus groups with patients (n = 35; 71% female, average age 45.2), community leaders (n = 5, 75% female, average age 48.1) and healthcare providers (n = 6, 16% female, 83% white, average age 51.2 years) to inform message concepts. Heuristic testing was conducted with community members to refine the intervention (n=9). All data collection was focused on barriers preventing diagnosis and treatment of sleep apnea. This paper presents results of the qualitative analyses conducted to inform the design of community-engaged, tailored sleep educational messages. Results: Analysis illuminated key barriers to sleep apnea, including: 1) low knowledge about the connection between daytime somnolence and sleep difficulties; 2) embarrassment about the interdependence between snoring and sleep apnea; and 3) inadequate healthcare access for effective treatments. Key messages for the TASHE intervention were based on existing scientific knowledge regarding sleep apnea diagnosis and treatment, while acknowledging the themes identified in the heuristic testing. Overall, participants rated the intervention high on usability (mean=5.0), user-friendliness (mean=4.9), and attractiveness (mean=4.3). Conclusion: The approach outlined here has potential for serving as a model to develop tailored interventions to bolster health communication in health disparities contexts. We found that tailoring can enhance potential persuasive outcomes of a behavioral intervention in the pre-testing phase prior to dissemination. Support (If Any): This work was supported by funding from the NHLBI (R25HL116378). Dr. Williams supported by funding from the NIH/NHLBI K23HL129359.